(untitled) (Research, Society and Development, 2022)
Introduction: Healthy aging and quality of life has become a great desire of contemporary society, as people are living longer, and the pursuit of a healthy life is paramount for the elderly. However, the sexuality of the elderly still refers to prejudiced and unrealistic stereotypes, being a taboo among the elderly. It is necessary to end these stigmas that society delegates to elderly people. Objective: To analyze aspects of sexuality in the elderly and the intervention of the physical therapist. Methodology: bibliographic review, exploratory descriptive. The research took place from February to April 2022. The data collected were on the virtual platform PUBMED, SciELO, from 2015 to 2020. Results and Discussion. Sexuality is not attributed only to the sexual act, it is based on affection, affection. However, society is prejudiced in relation to the sexuality of the elderly, with a view that he is a fragile and incapable person, so there is a ban on the elderly to remain sexually active. Sexuality is still little explored by health professionals. The role of the physical therapist is still recent. Conclusion: The professional is faced with many prejudices, and shyness of many elderly people in their daily work. There needs to be changes in the family and society in relation to the active sexual life of the elderly. In this part, the physical therapist is a professional who welcomes and works with functional problems that can affect the elderly’s bodily continuity in their sexual activity.